Characteristics and onsite costs of the sediment lost by runoff from Dapo and Chekorsa Watersheds, Digga District - Wudneh, A. (Ambo University, 2012)
This study conducted in two sub catchments of the Abay Basin identified the quantity and quality of sediment loss and its origin though most studies conducted in Ethiopia focus on quantification of soil loss. Also, the onsite economic cost in terms of yield reduction was estimated taking maize (Zea mays) as representative crop. For this purpose, two monitoring stations were selected at the outlet of the two watersheds. Depth integrated runoff samples were collected during the rainy season in 2011 while discharge of the Rivers was estimated from staff gauge-discharge relationship. Daily runoff samples were bulked for ten consecutive days and filtered to separate the sediment from the water. The water and sediment were subsampled for oven dry to determine sediment concentration and for chemical analysis to determine the Nitrogen and Phosphorus content at Ambo University laboratory. The difference in sediment concentration between the two Rivers was statistically significant. Regression analysis between that suspended sediment concentration is related to discharge for Dapo River (R2=0.7) but this relation was very weak for Chekorsa River (R2=0.286). The concentration of the plant nutrients considered was greater in the sediment delivered to the outlet than that of the original surface soil. The concentration of available P in the sediment was 2.7 to 9 times its concentration in surface soil from Dapo river catchment and Chekorsa river catchment, respectively. The soil nutrients in the sediment and surface soil of the lower and upper catchment were used to identify sediment source areas using a quantitative composite sediment fingerprinting method with 87% of source type correctly classified. The contribution of the upper stream part to the sediment load of River Dapo was greater than its downstream part, with values ranging from 37% to 67% using Total Kjeldal Nitrogen, and 44% and 56% using organic carbon to nitrogen ratio but in average 56% to 63%. Mean lost of available nitrogen and phosphorus was 1.6+0.14 and 0.4+0.06, and 1.5+0.17 and1.1+0.13 in Kg per decade from Chekorsa and Dapo River, respectively. As a result, the estimated onsite cost to farmers due to loss of nitrogen and phosphorus throughout the study period was about 3321 and 4975 Birr ha-1 for Dapo, and 3545 and 2324 Birr ha-1 for Chekorsa catchments in that order. The study therefore helps to understand the processes and cause of nutrient loss at a micro watershed level and to implement targeted management interventions.